APLIKASI BEBERAPA JENIS PUPUK ORGANIK PADA PERTUMBUHAN DAN PRODUKSI PADI SAWAH METODE SRI (SYSTEM OF RICE INTENSIFICATION) - Paulus, J. M.; Senduk, Jein H. (EUGENIA, 2016)
ABSTRACT The aim of the research was to studied the growth and production of rice with SRI methods as a response to application some type of organic fertilizer.  The field experiment was conducted in Tara Tara Village, Tomohon North Sulawesi for 5 months. The research arranged in Randomized Block Design with the treatmentof several types of organic fertilizers (PO) : without PO+100 % NPK (P0), PO market waste + 40% NPK (P1), PO legum (P2) + 40% NPK,  PO rice straw (P3) + 40% NPK, and  PO mix + 40% NPK (P4).The result showed that application of some type of organic fertilizer  were significant effect to plant height, number of tillers, number of grains per panicle, 1000 grain weight, and grain yield, except percentage pithy grain per panicle.  The highest of grain yield achieved by the treatment of PO rice straw + 40% NPK and PO legum + 40 % NPK, i.e 9,03 t ha-1 and 8,62 ton ha-1Key words : organic fertilizer,  rice, SRI (System of Rice Intensification)